2018
DOI: 10.2147/ott.s161109
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NFκB-signaling pathway in cancer

Abstract: Cancer is a group of cells that malignantly grow and proliferate uncontrollably. At present, treatment modes for cancer mainly comprise surgery, chemotherapy, radiotherapy, molecularly targeted therapy, gene therapy, and immunotherapy. However, the curative effects of these treatments have been limited thus far by specific characteristics of tumors. Abnormal activation of signaling pathways is involved in tumor pathogenesis and plays critical roles in growth, progression, and relapse of cancers. Targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
218
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(248 citation statements)
references
References 147 publications
4
218
0
3
Order By: Relevance
“…The nuclear factor kappa B (NFκB) family comprises of five DNA-binding proteins (p50, p52, p65, cRel, and RelB) that differentially modulate the transcription of genes that are involved in various cellular processes such as inflammation, migration, invasion, angiogenesis, proliferation, and apoptosis [172,173]. The continuous activation of NFκB has been reported in different types of cancers.…”
Section: Nuclear Factor Kappa B (Nf-κb)mentioning
confidence: 99%
“…The nuclear factor kappa B (NFκB) family comprises of five DNA-binding proteins (p50, p52, p65, cRel, and RelB) that differentially modulate the transcription of genes that are involved in various cellular processes such as inflammation, migration, invasion, angiogenesis, proliferation, and apoptosis [172,173]. The continuous activation of NFκB has been reported in different types of cancers.…”
Section: Nuclear Factor Kappa B (Nf-κb)mentioning
confidence: 99%
“…It is well accepted now that low-grade chronic inflammation is a major cause for a number of diseases, including cancer [5,6]. The transcription factor nuclear factor-kappaB (NF-κB), as a common responder to varied stress stimuli, leading to chronic low grade inflammation, plays a key role here [7,8]. This master regulator of inflammation is located as an inactive form in the cytoplasm and, after activation, shuttles to the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is activated by various cytokines, pathogens or growth factors [8,11]. Previous studies have shown that TNF-β (lymphotoxin), a member of the tumor necrosis factor family, induces inflammatory effects in CRC cells with a similar potency to TNF-α [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of NFκB-signaling on patient outcome are yet to be determined, but some studies indicate that chronic activation promotes a tumor growth-favorable environment. For example, studies have shown that NFκB activity can promote tumor cell, can suppress apoptosis, and can enhance vascular growth [12,13]. Furthermore, it can energize the immune system in certain circumstances [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that NFκB activity can promote tumor cell, can suppress apoptosis, and can enhance vascular growth [12,13]. Furthermore, it can energize the immune system in certain circumstances [13]. However, contradicting results for its role in cancer has also been documented; one recurring theme in immunology is that chronic proinflammatory signaling can contribute to carcinogenesis, while acute signaling can cause antitumor immune responses [14].…”
Section: Introductionmentioning
confidence: 99%